2000
DOI: 10.1161/01.hyp.35.1.231
|View full text |Cite
|
Sign up to set email alerts
|

Increased Nitrovasodilator Sensitivity in Endothelial Nitric Oxide Synthase Knockout Mice

Abstract: Abstract-Endogenously produced nitric oxide (NO) modulates nitrovasodilator-induced relaxation. We investigated the underlying mechanism in wild-type (WT) mice and endothelial NO synthase knockout (eNOS Ϫ/Ϫ ) mice to determine whether a chronic lack of endothelial NO alters the soluble guanylyl cyclase (sGC) pathway. In aortic segments from eNOS Ϫ/Ϫ mice, the vasodilator sensitivity to sodium nitroprusside (SNP) was significantly greater than that in WT mice. There was no difference in sensitivity to the G-kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
87
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 26 publications
22
87
1
Order By: Relevance
“…However, after endothelium denudation, the potency of GTN was potentiated in both groups (pEC 50 : 7.75 Ϯ 0.01 and 7.82 Ϯ 0.01, control vs. obese, respectively; data not shown). It has been reported that the endothelium-independent relaxations induced by NO donors are potentiated in eNOS knockout mice (34) or not affected after endothelium denudation in rats (35). Our results demonstrate a significant decrease in the potency of GTN in endotheliumintact aorta of obese rats.…”
Section: Effects Of Blockade Of Proximal Activators Of Enossupporting
confidence: 50%
“…However, after endothelium denudation, the potency of GTN was potentiated in both groups (pEC 50 : 7.75 Ϯ 0.01 and 7.82 Ϯ 0.01, control vs. obese, respectively; data not shown). It has been reported that the endothelium-independent relaxations induced by NO donors are potentiated in eNOS knockout mice (34) or not affected after endothelium denudation in rats (35). Our results demonstrate a significant decrease in the potency of GTN in endotheliumintact aorta of obese rats.…”
Section: Effects Of Blockade Of Proximal Activators Of Enossupporting
confidence: 50%
“…A similar decrease in NO-induced vasorelaxation has been reported in aorta of streptozotocin-induced diabetic rats due to decrease in guanylate cyclase and protein kinase G-protein (Zanetti et al, 2005). Interestingly, the activity of guanylate cyclase was increased in eNOS knockout mice (Brandes et al, 2000). Further experimentation is therefore necessary to clarify the involvement of guanylate cyclase and ROS in the mechanism by which elevated eNOS protein can alter Cx expression.…”
Section: Discussionsupporting
confidence: 60%
“…Brandes et al reported that both acute cessation of endothelial NO production in wild type mice and chronic deficiency of NO in eNOS knockout mice increase the NO sensitivity of vascular smooth muscle cells in response to nitrovasodilator agents [6]. They proposed that an enhanced sensitivity of soluble guanylate cyclase (sGC) to NO may compensate for the reduced NO availability [6].…”
Section: Impact Of Oxidative Stress On Coronary Arteriolar Smooth Musmentioning
confidence: 99%
“…They proposed that an enhanced sensitivity of soluble guanylate cyclase (sGC) to NO may compensate for the reduced NO availability [6]. In this context, it has been also found that administration of exogenous NO decreased sGC activity acutely and decreased its protein expression over time [43].…”
Section: Impact Of Oxidative Stress On Coronary Arteriolar Smooth Musmentioning
confidence: 99%
See 1 more Smart Citation